Analisis Fuzzy Sugeno Dalam Menentukan Pemilihan Motor Honda - Khairul Saleh; Helmi Fauzi Siregar; Zunaida Sitorus ((JurTI) Jurnal Teknologi Informasi, 2021)
Motorcycles are two-wheeled vehicles. Honda is one of the best selling motorcycle brands in Indonesia. Honda is a Japanese company that has been very tested in Indonesia. Honda also has many types, because of the many types of Honda motorcycles, a decision support system (DSS) with the fuzzy Sugeno method is needed in overcoming the selection of Honda motorcycles. At the same time to compare previous research that has been done with the Mamdani method in determining the selection of the Honda motorcycle.